Effects of Tai Chi and Aerobic Exercise on Lipid Levels, Inflammatory Response, and Vascular Endothelial Function in Patients with Coronary Artery Disease - Li, Yameng; Li, Cuihan; Liu, Mingyu; Zhang , Jianwei; Lyu, Shaojun (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details